Uji Aktivitas Antibakteri Fraksi Ekstrak Daun Jotang (Sphagneticola trilobata L) terhadap Bakteri Eschericia coli - Ghalib Syukrillah Syahputra; Ibnu Rusyd; Arie Vonikartika; Zahara Zahara; Eka Febriyanti; Delladari Mayefis (Journal Clinical Pharmacy and Pharmaceutical Science, 2025)
Jotang (Sphagneticola trilobata) is a wild plant that has antibacterial potential. This study aims to determine the antibacterial activity of the n-hexane, ethyl acetate and methanol fractions of jotang leaf extract against Escherichia coli bacteria. Jotang leaves were extracted using methanol by maceration extraction method, followed by the fractionation stage using Liquid-Liquid Extraction method. The fractionation process uses n-hexane, ethyl acetate and methanol as solvents. Next step, each fraction was tested for antibacterial activity using the disc diffusion method. The concentrations of each fraction used were 200 µg/disc, 400 µg/disc, and 1000 µg/disc, positive control used chloramphenicol and negative control used DMSO 10%. The Result showed the most potential antibacterial activity of the active fraction from jotang leaves extract was the n-hexane fraction.